Programa de escolarização para adolescentes em regime de internação - Erlich, Vanessa Harmuch Perez (2017)
School deficit and moral behavior are considered risk factors for the development of antisocial behavior. The objective of this study was to apply and evaluate an individual schooling program in the form of school reinforcement and moral behavior (Gomide, 2010) with adolescents in detention. The sample consisted of 20 adolescents: 10 of whom participated in the activities in two distinct groups (Pilot, with 4 participants and Principal, with 6) and 10 in the control group. The schooling activities were carried out in a range of 12 to 18 weeks with 02 to 04 hours a week and those of moral behavior for a period of 05 to 07 weeks with 02 to 04 hours a week. The evaluation instruments (TDE, WASI and YSR) were applied in pre- and post-tests. The results suggest the effectiveness of the program to increase knowledge related to school content (increase of 16.7 points in the average of QIT-4 and 11 points in the average of TDE in the Target Group 2) and reduction of internalizing, externalizing and total problems, with a decrease of 3 points for the same group. However, it is suggested to carry out more experimental research such as this, focusing on the possible control of the variables identified as obstacles in obtaining more expressive results, mainly training / engagement of the institution's team to act as multipliers of the concepts, and attention to the application of data measurement instruments.